Productive and structural traits of marandu grass pasture in response to supplemental bovine feeding levels and grazing cycles - Gomide, Carlos Augusto Miranda; Reis, Ricardo Andrade; Similli, Flávia Fernanda; Moreira, Andrea Luciane (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the productive and structural traits of marandu grass (Brachiaria brizantha cv. Marandu) pasture in response to supplemental bovine feeding levels and to grazing cycles. The evaluated levels of concentrate feeding based on citric pulp, corn, soybean meal and urea were: 0.2, 0.6, and 1 % body live weight. A completely randomized block design was used, with split plots in time, in which supplementation levels were the plots and grazing periods were the subplots. Supplemental feeding levels affected the grass canopy traits. Changes were detected in leaf area index, light interception, and leaf/stem ratio under pre-grazed pasture conditions. The lowest figures were observed for the supplementation level of 0.2% live weight. Under the post-grazing conditions, leaf biomass and the leaf/stem ratio traits were also least under the 0.2% supplemental feeding level. The structural and productive pasture traits, as well as the pasture morphogenetic indices exhibited effects of the grazing cycles. While dead material increased, tiller number and mass did not vary with the grazing cycles. The supplemental feeding of animals affected the marandu grass pasture traits. As the grazing season progressed from summer to autumn, pasture growth decreased and pasture structure was affected.